(untitled) (Physical Education, Health and Social Sciences, 2025)
This quantitative study examines the relationship between Karachi University students’ self-reported metacognition components and their reading comprehension performance. The study involved 100 undergraduate students, 50 from public universities and 50 from private ones. The study concentrated on how students’ self-reported using planning and evaluation-related metacognitive strategies affected their performance on reading comprehension tasks with inferential questions. The findings showed that the metacognitive elements of planning and assessment could explain a sizable amount of the variation in students’ inferential comprehension performance. These results highlight how important metacognitive awareness is for deciphering implicit meanings and making deductions while reading. The study emphasises the need for focused teaching methods that promote metacognitive growth to improve ESL students’ inferential reading abilities in higher education.